A new species and new records of Arrhopalitidae (Collembola: Symphypleona) from the Republic of Moldova - Vargovitsh, Robert S.; Buşmachiu, Galina (Zootaxa, 2015)
Eight species of the family Arrhopalitidae Stach, 1956 are listed from the Republic of Moldova. A new species, Arrhopalites prutensis sp. nov. is described. It belongs to the diversus group of species with 3, 2, 1, 1 anterior setae on dens, possesses neosminthuroid seta on the furca base region—a character rarely noted for the family. The new species is closely related to A. baccettii Dallai, 1969 and A. antonioi Giuga & Jordana, 2013 described from Sicily. Five species of the family are firstly recorded for the country.